The Influence of Marketing Mix on Meeting Package Purchase Decisions at Hotel XYZ - Setyani, Nyoman Amy Trisna; Kusumarini , Indah; Asmarani, I G A Ratih (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This research aims to determine the effect of the marketing mix (X) on purchasing decisions (Y) meeting package at Xyz hotel. Research data was collected by distributing questionnaires, documentation studies, and interviews. The method used is quantitative with Multiple Linear Regression data analysis techniques, t test, F test, coefficient of determination (R2), and calculation of Effective Contributions (SE), processed using SPSS Version 25. The population in this study are consumers meeting package as many as 90 respondents who have been determined by technique purposive sampling. Based on the results of the t test, it is known that the t value product (-0,277 > -1,989), people (1,775 < 1,989), process (0.441 < 1.989). Based on the results of the F test, it is known that the value of F-count > F-table (19.733 > 2.123) means that the 7P marketing mix has a significant effect on purchasing decisions. meeting package. Based on the Coefficient of Determination Test (R2) it is known that the marketing mix (X) has an influence of 62.7% on purchasing decisions (Y), while the rest is explained by other variables not discussed in this research. Based on the results of the Effective Contribution (SE) calculation, it shows that the variable physical evidence (X7) has a higher contribution of 13.3% to purchasing decisions (Y). Meanwhile, variable product (X1) has a lower contribution of 1.54% to the purchase decision (Y).